ANALYSIS OF COMMUNITY PARTICIPATION IN ACHIEVING THE FIRST PILLAR OF COMMUNITY-BASED TOTAL SANITATION AT UPT PUSKESMAS SIPEA-PEA, WEST SORKAM SUB-DISTRICT, CENTRAL TAPANULI DISTRICT YEAR 2023 - Simamora, Elsiana; Sirait, Asima (Akupun Tour Publisher, 2023)
Background: Environmental health issues are still one of the focus of health problems in Indonesia. In this regard, in order to support the achievement of the National Medium-Term Development Plan (RPJMN) targets including Universal Access 2019, by the end of 2019 100% of villages must implement Community-Based Total Sanitation (STBM), and 50% of STBM villages must achieve verified Open Defecation Free (ODF). In this case the government produces a new paradigm, namely giving a greater role to the community and placing it as the object as well as the subject of development. Purpose: The purpose of this study is to determine the forms of community participation, to determine the level of participation, and to determine the factors that influence community participation in Pasaribu Tobing Jae Village. This type of research uses qualitative research with a phenomenological approach. Method: The data collection is obtained from observations to see facts in the field, interviews and documentation. Using research informants taken from respondents who are responsible for determining policies and decisions and supervision related to the implementation of the STBM Program, Head of Puskesmas, Sanitarian Officers, community leaders and Communities who participate in the STBM program in Pasaribu Tobing Jae Village. Results: The results show that the form of participation of thinking and giving energy has been carried out in the development of the program, but in the form of property participation the community has not provided financial assistance or property in the implementation of STBM, for the level of participation of each informant, participating based on their respective levels of participation, and for factors that influence the community to participate, namely economic factors, knowledge and attitudes that are still low towards caring about latrine construction. Disscusion and Conclusion: Suggestions for optimizing the work of puskesmas sanitarians in triggering socialization through community involvement in planning, development to pre-triggering evaluation.